Influence of Aging on the Dopaminergic Neurons in the Substantia Nigra Pars Compacta of Rats - Gao, Jin; Miao, Hui; Xiao, Cheng-hua; Sun, Yu; Du, Xia; Yuan, Hong-hua; Yu, Hong-li; Gao, Dian-shuai (Current Aging Science, 2011)
To study the relationship between aging and the vulnerability of substantia nigra pars compacta (SNc) tyrosine hydroxylase immunoreactive positive (TH+) dopaminergic (DA) neurons. We determined the number of TH+ DA neurons in aged rats (24 mon) compared to adult rats (5 mon) using immunohistochemistry and cell counting. Furthermore, the expression of TH mRNA and protein levels in SN was studied by semi-quantitative RT-PCR and Western blotting. A 13.6% loss of neurons was detected in rostral segment of SNc, and the expression of TH mRNA levels was also reduced (P < 0.05), however, no difference was detected in TH protein levels (P > 0.05). These data suggest that expression of TH protein may increase in the existing SNc DA neurons, which may compensate for the partial loss of TH+ DA neurons.
Keywords: dopaminergic (DA) neurons